(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In this study, the antibacterial and anti-cancer activities of Daucus carota kanji, a traditional fermented beverage, were investigated. Kanji was prepared through the fermentation of carrots with spices over 7-10 days, allowing lactic acid bacteria (LAB), primarily Lactobacillus plantarum and Lactobacillus fermentum, to proliferate. Microbiological analysis confirmed a significant rise in LAB count from negligible on day 0 to 8.2 × 10⁶ CFU/mL on day 7. The antibacterial activity of kanji extract, tested against Staphylococcus aureus, Escherichia coli, Salmonella enterica, and Listeria monocytogenes, demonstrated dose-dependent inhibition, with the largest zones of inhibition observed at 20% concentration, particularly against Gram-positive strains. Characterization tests confirmed the presence of Gram-positive, catalase-negative LAB strains, consistent with lactic acid bacteria characteristics. In vitro studies on HGT-1 gastric cancer cells revealed that kanji extract significantly reduced cell viability in a dose-dependent manner, with the highest concentration (20%) reducing cell viability to 55% after 72 hours. The reduction in cancer cell viability was attributed to the bioactive compounds produced during fermentation, including lactic acid, phenolic compounds, and flavonoids. These results highlight kanji's potential as a natural antibacterial agent and its possible application as a complementary therapeutic for cancer treatment. Further research is recommended to explore its mechanisms of action and potential health benefits.